Predictors of the occurrence of cardiovascular events in patients with atrial flutter during long-term follow-up - A.V. Aker; U.P. Chernyaga-Royko; N.S. Pavlyk; O.J. Zharinov (Кардіохірургія та інтервенційна кардіологія)
The aim – to identify factors associated with the occurrence of cardiovascular events in patients with non-valvular AFL during prolonged prospective follow-up. Materials and methods. The one-center prospective study included 126 patients with various forms of AFL, among them 86 (68.3 %) men and 40 (31.7 %) women, median age 65.5 (quartile 55–73) years. During 8 months follow-up, death or cardiovascular events developed in 41 patients. All patients were retrospectively divided into two groups: patients without complications (n = 85) and those with primary end point (n = 41). Results. There were no significant differences between two groups regarding age and sex. Patients with events have had MI earlier (11 (12.9 %) vs 16 (39.0 %), p = 0.002), they had a slightly higher risk of thromboembolic events over CHA2DS2-VASc score (p = 0.062). In the second group hemodynamic disorders were more frequently observed in the index episode (17.1 % vs. 3.5 %, p = 0.03) and sinus rhythm was less frequently recorded at the time of discharge from hospital 20 (48.7 %) vs 58 (68.2 %), p = 0.049) compared to patients without complications. Conclusions. The main predictors of the occurrence of cardiovascular events in hospitalized patients with AFL were the presence of myocardial infarction, hemodynamic disturbances during the paroxysm of AFL, as well as transforming to permanent AFL.